2017
DOI: 10.1111/1756-2171.12192
|View full text |Cite
|
Sign up to set email alerts
|

Mergers with interfirm bundling: a case of pharmaceutical cocktails

Abstract: Pharmaceutical cocktails often consist of two or more drugs produced by competing firms. The component drugs are often also sold as stand‐alone products. We analyze the effects of a merger between two pharmaceutical firms selling complements for colorectal cancer treatment. In this setting there are two merger effects: the standard upward pricing pressure due to firms internalizing the substitution between the stand‐alone products, and an additional effect where the firms internalize the impact of selling comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…An essential factor behind the practical advantages of the proposed C2SLS estimator is the use of individual-level purchases in the aggregate form of bundle-level purchase probabilities. Bundle-level purchase probabilities are not typically directly observed (with the exception of a few industries, see Crawford and Yurukoglu, 2012;Song et al, 2017) but rather computed from samples of individual-level purchases (Ershov et al, 2021) and thus subject to sampling error. When the number of bundles is large relative to the sample of individual-level purchases, sampling error in the bundle-level purchase probabilities can be pronounced and lead to estimation bias (Gentzkow et al, 2019), for example because of the large number of observed "zeros" (Gandhi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An essential factor behind the practical advantages of the proposed C2SLS estimator is the use of individual-level purchases in the aggregate form of bundle-level purchase probabilities. Bundle-level purchase probabilities are not typically directly observed (with the exception of a few industries, see Crawford and Yurukoglu, 2012;Song et al, 2017) but rather computed from samples of individual-level purchases (Ershov et al, 2021) and thus subject to sampling error. When the number of bundles is large relative to the sample of individual-level purchases, sampling error in the bundle-level purchase probabilities can be pronounced and lead to estimation bias (Gentzkow et al, 2019), for example because of the large number of observed "zeros" (Gandhi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…9 The MNL implies that the unobserved preferences of any two bundles are independent. The NL instead requires every bundle to belong uniquely to one nest, so that either all bundles have equally correlated preferences (a unique nest) or some of the bundles with overlapping components end up with uncorrelated preferences (more than one nest, Song et al, 2017). We return to this point below.…”
Section: The Product-overlap Nested Logit (Ponl) Modelmentioning
confidence: 99%
See 2 more Smart Citations